Rayner Complex and Western Rayner Complex in Enderby Land - Hokada, Tomokazu; Baba, Sotaro; Kamei, Atsushi; Kitano, Ippei; Horie, Kenji; Motoyoshi, Yoichi; Hiroi, Yoshikuni; Shiraishi, Kazuyuki; Takehara, Mami (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences, Wed. 5 Dec. / 3F Seminar room, National Institute of Polar Research conference object